’Hustle Culture’ vs ‘Slow Living’: Finding Work-Life Balance in the Modern World - Ulya, Latifatul (Maliki Interdisciplinary Journal, 2025)
This article discusses two contrasting yet highly relevant lifestyle phenomena in the modern world: ‘Hustle Culture’ and ‘Slow Living’. ‘Hustle Culture’ describes a lifestyle that demands hard work, high productivity, and constant busyness as the keys to success and career achievement. Meanwhile, ‘Slow Living’ offers an alternative by emphasizing mindfulness, a more relaxed approach to time management, and a focus on quality of life and mental well-being. This article also discusses the psychological and social impacts of these two cultures, including the risks of burnout and stress that often arise in practitioners of ‘Hustle Culture’, as well as the mental health benefits and life satisfaction that can be gained through the application of ‘Slow Living’. By examining the strengths and weaknesses of each approach, this article provides a perspective on how individuals can integrate both concepts to create an optimal balance between work and personal life. This finding is important to help people cope with the pressures of modern life without sacrificing mental health and quality of life.